Cellular Response to Reagent-Free Electron-Irradiated Gelatin Hydrogels - Wisotzki, Emilia I.; Friedrich, Ralf P.; Weidt, Astrid; Alexiou, Christoph; Mayr, Stefan G.; Zink, Mareike (Macromolecular Bioscience, 2016)
As a biomaterial, it is well established that gelatin exhibits low cytotoxicity and can promote cellular growth. However, to circumvent the potential toxicity of chemical crosslinkers, reagent-free crosslinking methods such as electron irradiation are highly desirable. While high energy irradiation has been shown to exhibit precise control over the degree of crosslinking, these hydrogels have not been thoroughly investigated for biocompatibility and degradability. Here, NIH 3T3 murine fibroblasts are seeded onto irradiated gelatin hydrogels to examine the hydrogel's influence on cellular viability and morphology. The average projected area of cells seeded onto the hydrogels increases with irradiation dose, which correlates with an increase in the hydrogel's shear modulus up to 10 kPa. Cells on these hydrogels are highly viable and exhibits normal cell cycles, particularly when compared to those grown on glutaraldehyde crosslinked gelatin hydrogels. However, proliferation is reduced on both types of crosslinked samples. To mimic the response of the hydrogels in physiological conditions, degradability is monitored in simulated body fluid to reveal strongly dose-dependent degradation times. Overall, given the low cytotoxicity, influence on cellular morphology and variability in degradation times of the electron irradiated gelatin hydrogels, there is significant potential for application in areas ranging from regenerative medicine to mechanobiology.
EVALuna2:33220